Problematizing Speaking Anxiety in Language Learning Settings: Some Relevant Considerations and Insights - Bula Villalobos, Olmedo (2023)
It is thus important to have a deep understanding of such a phenomenon and its implications. The aim of this paper is to problematize speaking anxiety in order to have a solid understanding of this situation and its potential implications within language learning contexts. Another purpose is to explore the literature on strategies used by learners to handle speaking anxiety. Likewise, the paper is to offer an overarching panorama of such a phenomenon within the field. It comprises seven sections containing relevant considerations and insights. The paper adopted an exploratory methodology that included a systematic revision of information on the phenomenon. The main conclusion establishes speaking anxiety as a significant issue that impacts students’ performance in language learning settings.